Inter-segmental coordination in progressions for the longswing on high bar - Irwin, G.; Kerwin, D. G. (Sports Biomechanics, 2007)
This study focused on identifying the most effective skill progression for developing the longswing on high bar in men's artistic gymnastics. Building on previous work by Irwin and Kerwin (2005), in which a method to rank progressions based on their angular kinematics was developed, this study aimed to use the method to quantify similarities in inter-segmental coordination between selected progressions and the longswing on high bar. Video images of four members of the UK men's national gymnastics squad performing three series of five longswings and eight progressions were recorded at 50 Hz. Two-dimensional direct linear transformation techniques were used to determine the real-world coordinates from the digitized data. Inter-segmental coordination of the hip and shoulder joints during the functional phases of the longswing was assessed using continuous relative phase. Similarity between the longswing and each progression was represented by a "specificity score", which was also used to rank the progressions. Each progression's specificity score was calculated by combining a "difference score" (root mean squared difference between the continuous relative phase profiles of the longswing and the progression) and a "variability score" (standard deviation of the continuous relative phase profiles for each progression). The progressions that were most similar to the longswing included the looped bar longswing and layaway swing down (ranked 1st and 2nd), with specificity scores of 9% and 10% respectively. In contrast, the least similar progressions were the looped bar "no action" longswing (51%) and pendulum swing (63%) (ranked 7th and 8th). Establishing effective skill learning pathways is recognized as a key component of the coaching process and ranking progressions based on their specificity score provided a mechanism to identify progressions with similar inter-segmental coordination profiles to the key skill on the high bar, the longswing.